Guidelines for the Development of the Management Potential of cultural tourism : A case study of Phra That Phanom, That Phanom District, Nakhon Phanom Province: แนวทางในการพัฒนาศักยภาพการบริหารจัดการแหล่งท่องเที่ยวเชิงวัฒนธรรมโดยการมีส่วนร่วมของชุมชน กรณีศึกษา : พระธาตุพนม อำเภอธาตุพนม จังหวัดนครพนม - Noppanatwongsakorn, Rachen (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were 1) to study ways to develop the potential for cultural tourism management with community participation and 2) to study problems and obstacles in the development of cultural tourism through community participation. This research was a qualitative research using in-depth interview as a data collection tool. Key informants are tourists. community group and a group of 38 community leaders using a purposive sampling method. The data were analyzed by taking content from in-depth interviews for content analysis and descriptive compilation. The results of the research revealed that 1) The approach for developing the potential of cultural tourism management is to develop a master plan to cover the development of cultural tourism management both in the short term and in the long term. and 2) Major problems and obstacles in the development of cultural tourism were: Lack of publicity through various media thoroughly. improvement of road conditions service quality of staff Encouraging people in the community to take part in the management of more cultural tourism.